ODPOWIEDZIALNOŚĆ ZSRR ZA NARUSZENIA PRAWA MIĘDZYNARODOWEGO W STOSUNKU DO POLSKI W LATACH 1939-1945 - Krzysztof Czubocha (Zeszyty Prawnicze)
International Responsibility of the Soviet Union for its Illegal Actions against Poland between 1939 and 1945